Elaboración de un texto didáctico interactivo de programación en lenguaje estructurado para el proceso enseñanza-aprendizaje en los estudiantes de segundo año de bachillerato de la Unidad Educativa Ismael Pérez Pazmiño del cantón Machala periodo lectivo 2012-2013. - Torres Ríos, Virgilio Alberto (2013)
I investigate this work is an aid for teachers in the area of ​​IT, because through it can impart much better his professorship because educational institutions do not have interactive teaching module texts structured programming language.